Análisis y sistematización del diseño e implementación del modelo escalable de alianzas multiactor para la provincia de Condorcanqui (departamento de Amazonas) entre el periodo 2018 - 2021 - Bolaños Chavarri, Francisco José (2022)
This work employs a qualitative methodology for the action-research design that collects experience from the AMA, which is based on the Territorial Approach and Strategic Planning during its implementation in Condorcanqui Province and its further scaling from 2018 to 2021. During this period, the leadership of the SGTD PCM was strengthened and the model was installed in three regions: Amazonas, Tumbes and Cajamarca. Additionally, the actors were integrated into a roadmap that leads its actions from planning digital territories, which are established by the SGTD PCM. The study analyzes the actions and procedures of the multi-stakeholder lead team organizing the workshops and worktables. Those allow to conduct research, apply methodology, establish agreements and to organize resources for integrated strategic planning results. The relevance of the AMA process is concentrated in the GE team, being the object of systematization. For this reason, the results of applying management instruments and tools are analyzed; their level of empowerment; their escalation; their roles and commitments; as well as the level of representation of public, private and academic actors. The objective of this research is to develop process systematization to record the generated information, develop analysis resources and understanding that guarantees its replication and escalation at different levels and scales. Finally, this work offers a systemic analysis of GEI, allowing to know: the opportunities and limitations of the GEI team, the mechanisms that facilitated the integration of the actors, the organization to structure the processes, propose a methodological platform of management for its escalation in other territories and that its results serve as a training reference.